Immune profiling of experimental murine mastitis reveals conserved response to mammary pathogenic Escherichia coli, Mycoplasma bovis, and Streptococcus uberis - Schneider, Peleg; Salamon, Hagit; Weizmann, Nathalie; Nissim-Eliraz, Einat; Lysnyansky, Inna; Shpigel, Nahum Y. (Frontiers in Microbiology, 2023)
Mastitis is one of the most prevalent and economically important diseases of dairy animals. The disease is caused by ascending bacterial infection through the teat canal. Among the most common mastitis-causing bacteria are gram-negative coliforms, gram-positive streptococci and staphylococci, and mycoplasma. The most prominent cellular hallmark of acute mammary infection is a massive recruitment of blood neutrophils into the tubular and alveolar milk spaces. The complex biological processes of leukocyte recruitment, activation, adhesion, and migration in the mammary gland remain largely elusive to date. While field research of mastitis in dairy animals contributed a lot to the development of mitigation, control, and even eradication programs, little progress was made toward understanding the molecular mechanisms underlying the pathogenesis of the disease. We report here experimental mastitis model systems in lactating mice challenged with field strains of common udder pathogens in dairy cows. We used these model systems to apply recently developed multiplex gene expression technology (Nanostring nCounter), which enabled us to study the expression of over 700 immune genes. Our analysis revealed a core of 100 genes that are similarly regulated and functionally or physically interacting in E. coli, M. bovis and Strep uberis murine mastitis. Common significantly enriched gene sets include TNFɑ signaling via NFkB, Interferon gamma and alpha response, and IL6-JAK-STAT3 signaling. In addition, we show a significantly enriched expression of genes associated with neutrophil extracellular traps (NET) in glands challenged by the three pathogens. Ligand-receptor analysis revealed interactions shared by the three pathogens, including the interaction of the cytokines IL1β, IL1ɑ, and TNFɑ with their receptors, and proteins involved in immune cell recruitment such as complement C3 and ICAM1 (with CD11b), chemokines CCL3 and CCL4 (with CCR1), and CSF3 (with CSF3R). Taken together, our results show that mammary infection with E. coli, M. bovis and Strep uberis culminated in the activation of a conserved core of immune genes and pathways including NET formation.